KI-Mediated Three-component Reaction of Hydroxylamine Hydrochloride with Aryl/Heteroaryl Aldehydes and Two β-Oxoesters - Mosallanezhad, Asiyeh; Kiyani, Hamzeh (Orbital: The Electronic Journal of Chemistry, 2018)
A KI-mediated multi-component cyclocondensation of hydroxylamine hydrochloride, aromatic/hetero-aromatic aldehydes, and ethyl acetoacetate or 4-chloroethyl acetoacetate to form isoxazole-5(4H)-one heterocycles is described. The reaction employs readily accessible starting reactants and provides a range of synthetically isoxazole-5(4H)-ones in good to high yields. Reactions were performed in water as a green medium at room temperature (RT) without heating, microwave irradiation or sonication. Reusability of the reaction medium is also a noteworthy characteristic of this reaction. DOI: http://dx.doi.org/10.17807/orbital.v10i2.1134